Primary Bone Marrow Classical Hodgkin Lymphoma in HIV- Negative Population: Aggressive but Amenable - Bhagirathbhai R Dholaria; Daisy Alapat; Daisy Alapat; Konstantinos Arnaoutakis; Konstantinos Arnaoutakis (Mediterranean Journal of Hematology and Infectious Diseases)
Classical Hodgkin Lymphoma has distinct clinopathological features and good response to treatment in most cases. Primary bone marrow limited Hodgkin Lymphoma is uncommon and primarily described in HIV positive patients. It behaves like a distinct entity with aggressive clinical course and poor response to available treatments. We discuss here a case of Hodgkin Lymphoma with isolated involvement of the bone marrow in an HIV negative patient, successfully treated with conventional chemotherapy.